Advances in balloon pulmonary angioplasty for chronic thromboembolic pulmonary hypertension. (1st May 2021) - Mahmud, Ehtisham; Patel, Mitul; Ang, Lawrence; Poch, David
Abstract : Balloon pulmonary angioplasty (BPA) is an emerging treatment option for patients with chronic thromboembolic pulmonary hypertension (CTEPH) who have inoperable, segmental/subsegmental disease, or residual disease after pulmonary endarterectomy. In the past decade, advances in the techniques for BPA have led to better clinical outcomes with improvements in hemodynamics, pulmonary perfusion, exercise tolerance, functional capacity, and quality of life. We present the experience with BPA at our university, the largest CTEPH center in the world, followed by reviewing the published data regarding the efficacy and safety of BPA in patients with CTEPH. There is increasing evidence to support that the initial hemodynamic improvement is sustained for ≥3 years after the procedure. Although infrequent, complications observed with BPA are associated with pulmonary vascular injury or rarely reperfusion pulmonary edema. As the technique for percutaneous pulmonary artery revascularization has improved, the procedural risk and complications have continued to decrease. This promising technique continues to develop, and future research is required to demonstrate the long‐term benefits of BPA, standardize the technique, and define a uniform institutional infrastructure for providing BPA as a part of the treatment of CTEPH.